9 Effect of coffee consumption on arterial stiffness from UK biobank imaging study. (May 2019) - Fung, Kenneth; Biasiolli, Luca; Hann, Evan; Aung, Nay; Paiva, Jose; Lukaschuk, Elena; Sanghvi, Mihir; Carapella, Valentina; Rayner, Jennifer; Werys, Konrad; Puchta, Henrike; Thomas, Katharine; et al.
Abstract : Introduction: Coffee is widely reported to be the world's most popular drink and previous studies revealed acute increases in arterial stiffness with its consumption. But, the reported chronic effects of coffee on arterial stiffness are inconsistent and limited by modest number of studied subjects. This study aims to evaluate the association of coffee consumption on arterial stiffness using two forms of stiffness measures in a large population cohort. Aortic distensibility (AoD) is a local measure of arterial stiffness whilst arterial stiffness index (ASI) is a measure of wave reflection. Both measures have been shown to be predictors of cardiovascular events. Methods: This cross-sectional cohort analysis comprised of 17, 932 participants in the UK Biobank Imaging Study who underwent both cardiovascular magnetic resonance (CMR) imaging and pulse waveform measurements via finger probes. Participants with known cardiovascular disease were excluded. Coffee consumption habits were self-reported at the time of imaging and those who drink >25 cups/day were excluded. Coffee consumption was categorised into 3 groups (≤1, 1–3, >3 cups/day) with the lowest group used as the reference in the analyses. AoD was derived using an automated method to obtain the maximum and minimum luminal areas in the ascending (AA) and descending aorta (DA) from cine CMR images. ASI was calculated by dividing the participant's height by the time interval between the peaks of the waveform recorded. AoD and ASI outliers (1.5x inter-quartile range rule) were excluded. Log transformation of AoD values was performed prior to regression analyses. Associations between coffee consumption and stiffness measures were assessed separately using univariate linear regression models adjusting for age, sex, ethnicity, Townsend deprivation index, current smoking, higher levels of education, height, weight, regular alcohol consumption (≥3 times/week), systolic blood pressure, resting heart rate, presence of hypertension, hypercholesterolaemia or diabetes, intake of vegetable, meat, water and tea consumption. Results: Baseline characteristics of the 8, 412 participants included in the final analyses are summarised in table 1. Moderate and heavy coffee drinkers were more likely to be male, smoke and consumed alcohol regularly. No significant differences were observed in the systolic blood pressures and heart rates between the groups. The unadjusted distributions of AoD in AA and DA were similar across the 3 groups (figure 1 ). Our regression models found no statistically significant differences in all three arterial stiffness measures for individuals who drink 1–3 cups or >3 cups of coffee/day compared with the reference group (table 2 ). Conclusion: In this large middle-aged cohort without cardiovascular disease, moderate to heavy coffee consumption was not associated with significant changes in arterial stiffness measured by AoD and ASI compared with individuals who drink ≤1 cups of coffee/day. Conflict of Interest: None